Evolutionary game analysis of the partners' behavior in the rural e-payment market of China - Jerzy W. Wiśniewski; Ewelina Sokołowska; Jinghua Wu; Anna Dziadkiewicz (Risks, 2021)
The rural e-payment market in China is becoming one of the important topics in the research field because of its contribution to the efficiency of fund flows in the economy. Further development of the rural e-payment market mainly depends on its partners' acceptance. In March 2020, 776.08 million people were using mobile payments in China. After the COVID-19 pandemic in China, the Payment and Clearing Association of China launched an action to encourage citizens to use mobile payments. In this article evolutionary game theory is presented. The benefits of e-payments between financial institutions and users are studied. Based on the analysis of the partners' selection of costs and profits as well as other factors, important conclusions were drawn. The growth of the rural economy is beneficial to the change of the partners' behavior in the rural e-payment market. Dynamic evolution of the partners' behavior makes the supply and demand for rural e-payment services consistent. In order to create more benefits, financial institutions will lead the move to merge the rural e-payment market with the China National Advanced Payment System. These research results are beneficial for its growth by developing strategies to encourage more partners to take part in the rural e-payment market in China.
Keywords: 330; rural finance; financial services; payment market; evolutionary game theory